Clinical Predictive Circulating Peptides in Rectal Cancer Patients Treated with Neoadjuvant Chemoradiotherapy. Issue 8 (August 2015) - Crotti, Sara; Enzo, Maria Vittoria; Bedin, Chiara; Pucciarelli, Salvatore; Maretto, Isacco; Del Bianco, Paola; Traldi, Pietro; Tasciotti, Ennio; Ferrari, Mauro; Rizzolio, Flavio; Toffoli, Giuseppe; Giordano, Antonio; et al.
<x xml:space="preserve">Abstract</x> Preoperative chemoradiotherapy is worldwide accepted as a standard treatment for locally advanced rectal cancer. Current standard of treatment includes administration of ionizing radiation for 45–50.4 Gy in 25–28 fractions associated with 5‐fluorouracil administration during radiation therapy. Unfortunately, 40% of patients have a poor or absent response and novel predictive biomarkers are demanding. For the first time, we apply a novel peptidomic methodology and analysis in rectal cancer patients treated with preoperative chemoradiotherapy. Circulating peptides (Molecular Weight <3 kDa) have been harvested from patients' plasma (n = 33) using nanoporous silica chip and analyzed by Matrix‐Assisted Laser Desorption/Ionization‐Time of Flight mass spectrometer. Peptides fingerprint has been compared between responders and non‐responders. Random Forest classification selected three peptides at m/z 1082.552, 1098.537, and 1104.538 that were able to correctly discriminate between responders (n = 16) and non‐responders (n = 17) before therapy (T0) providing an overall accuracy of 86% and an area under the receiver operating characteristic (ROC) curve of 0.92. In conclusion, the nanoporous silica chip coupled to mass spectrometry method was found to be a realistic method for plasma‐based peptide analysis and we provide the first list of predictive circulating biomarker peptides in rectal cancer patients underwent preoperative chemoradiotherapy. J. Cell. Physiol. 230: 1822–1828, 2015. © 2014 Wiley Periodicals, Inc.